Sosialisasi Pengembangan Usaha Mikro Para Pelaku Usaha di Kabupaten Penajam Paser Utara - Nurlia Nurlia; Amir Iskandar; Dwi Susilowati; Tutik Yuliani; Nadi Hernadi Moorcy; Tamzil Yusuf; Wiwik Saraswati; Umi Kasanah; Khofifah Oktavia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2023)
Micro businesses contribute to the economy of families and the government, therefore there needs to be attention to business actors. With the development of business actors it will be able to help the government in absorbing labor and overcoming the problem of unemployment. The importance of business actors for the government is that steps can be taken by identifying the potential of business actors in their own regions. North Penajam Paser Regency is one of the districts in East Kalimantan which has business actors in various businesses. Business actors in North Penajam Paser district have problems related to knowledge in developing their businesses. This Community Service aims to increase knowledge of business actors in North Penajam Paser Regency so they can develop their businesses. The result of this service activity is that business actors understand the need to develop their business and know how to develop the business they already have.